Enhancing Students’ Geometry Learning Outcomes and Critical Thinking Skills through the Implementation of Problem Based Learning Model - Dewi Indrapangastuti; Murwani Dewi Wijayanti; Achmad Basari Eko Wahyudi (STAI Hubbulwathan Duri, 2024)
To enhance students' critical thinking abilities, it is essential to adopt an interactive learning model where students actively participate, and the instructor acts as a facilitator. This can be achieved through the implementation of the Problem-Based Learning (PBL) model in the teaching and learning process. This study aimed to evaluate the improvement of learning outcomes and critical thinking skills through the application of the PBL model among students. Conducted as classroom action research, it involved 40 students from Yogyakarta State University. The research comprised two cycles, each consisting of two sessions. Instruments used included observation sheets for learning implementation, critical thinking assessment sheets, and tests. Data analysis was performed quantitatively using descriptive analysis methods. The findings revealed that (1) the learning process was effectively implemented, with observation data from both cycles rated as good, with a mode of 4 (good); (2) students' learning outcomes improved, with the average post-test scores increasing from 70.85 in Cycle 1 to 80.63 in Cycle 2; (3) students' critical thinking skills also enhanced, with the average score rising from 68.54 in Cycle 1 to 82.08 in Cycle 2. The conclusion of this study is that implementing PBL in the learning process can significantly enhance both critical thinking and learning outcomes. The research implies that teachers' professional competence can be developed through the application of PBL. It is recommended that teachers integrate the PBL model into their teaching practices to foster students' higher-order thinking skills, such as critical thinking, creativity, and scientific reasoning abilities.